ASSA14-03-07 Prenatal Lipopolysaccharide Exposure Results in Dysfunction of Renal Dopamine D1 Receptor in Offspring Rats. (1st December 2014) - Wang, X; Luo, H; Wang, J; Chen, C; Cai, Y; Zhen, S; Zhou, L; Zeng, C
Abstract : Objective: Adverse environmental exposure inuteropredisposes to adult disease, including hypertension. Exposure to lipopolysaccharide (LPS) results in increased blood pressure in offspring, but the exact mechanisms are not clear. Our previous study shows dysfunction of renal D1 receptor (D1 R) isascribed to the pathogenesis of hypertension, which is associated with reactive oxidativestress (ROS). In this study, we test whether dysfunction of renal D1 R is involved in fetal programmed hypertension, and whether oxidative stress contribute to this process. Methods: Pregnant Sprague–Dawley (SD) rats were intraperitoneally injected with LPS (0.79 mg/kg) or saline (0.5 ml) at gestation day 8, 10 and 12. After birth, the blood pressure is measured, and treated with or without antioxidant tempol in tap water for 3 weeks at postnatal 12 week. Results: As compared with control rats, the LPS-treated offspring rats showed higher blood pressure, decreased renal sodium excretion with increased plasma ROS activity. After treatment with tempol for 3 week, the increased blood pressure, decreased sodium excretion were reversed to normal levels in LPS rats. Our further study found LPS rats had lower renal D1 R expression, higher D1 R phosphorylation, and D1 R-mediated natriuresis and diuresis were lost. As an important kinase of D1 R phosphorylation, G coupled receptor protein kinase 4 (GRK4) expression was increased in LPS rats. Tempol treatment reversed the decreased D1 R expression, increased D1 R phosphorylation and GRK4 expression. Moreover, the impaired D1 R-mediated natriuresis and diuresis were restored to the control levels in LPS rats after tempol treatment. Conclusion: Pprenatal LPS exposure, via impairment of ROS on renal D1 R function, leads to hypertension in offspring. Reversion of renal D1 R function by alleviation of ROS might be a target for therapy of fetal programming hypertension.